An observational study on extraperitoneal caesarean section in present era - Nanda, Sudhanshu Sekhara; Dash, Subhalaxmi; Huria, Anju; Mehra, Reeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was designed to find out the maternal and perinatal outcome in cases of extraperitoneal caesarean section. Total 100 women undergoing extraperitoneal cesarean section were included in the study. Methods: A detailed history taking, examination done and intra and post-operative parameters as per protocols were noted. Results: Success rate of extra peritoneal CS was 79.63%, Time taken from incision to delivery was ≤5 minutes in 60% cases, time taken from incision to closure was between 31-45 min in 67% cases, blood loss ≤500 ml in 58% cases, return of bowel function between 5-8 hours in 52%, mobilization within 24 hours in 52%, neonatal one minute APGAR score ≥7 in 90.91%. Conclusions: Extraperitoneal cesarean section can be applied as a surgical form of infection prophylaxis.Since it possesses a rational basis for the avoidance of serious post-operative pelvic infectious complications, this operation deserves reconsideration in the modern era.